Central venous pressure monitoring in living donor kidney recipients does not affect immediate graft function: A propensity score analysis. Issue 5 (30th March 2018) - Adelmann, Dieter; Bicknell, Leonie; Niemann, Claus U.; Feiner, John; Roll, Garrett R.; Burdine, Lyle; Whitlock, Elizabeth L.
Abstract: Background: During kidney transplantation, intraoperative fluid management can affect post‐transplant graft function. It is unclear whether or not central venous pressure (CVP) monitoring is required to guide fluid therapy during kidney transplantation. Methods: We compared post‐transplant graft function in recipients of living donor kidney transplants between August 2006 and March 2009 based on the use or absence of intraoperative CVP monitoring. Graft function, assessed using the creatinine reduction ratio on postoperative day 2 (CCR2), was evaluated by multivariable linear regression analysis and in a propensity‐matched cohort. Results: Two hundred and ninety patients were included in the analysis. Central venous pressure was monitored in 84 patients (29%). There was no difference in post‐transplant graft function, as measured by CCR2, between patients with and without CVP monitoring in both unadjusted and multivariable‐adjusted analyses. There were also no statistically significant differences in CCR2, delayed graft function, or 3‐month renal function between those monitored with CVP and those without, in the propensity‐matched cohort. Conclusions: In this single‐center analysis, immediate post‐transplant renal function was not associated with the use of intraoperative CVP monitoring.